FACTORS INFLUENCING PERFORMANCE OF BANKING SECTOR LISTED ON INDONESIA STOCK EXCHANGE - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 13 No.2, 2014 JBE UNKLAB, 2014)
This study investigated some talent factors that can influence Indonesian banking performance to provide a framework by which business leaders could assess their current management capabilities. Using purposive sampling, 30 banks listed on Indonesia Stock Exchange in 2012 were selected. Corporate governance aspects were measured by employing five talent factors and banking performance was measured using profit per employee. Five hypotheses were tested using multiple regression analysis.  The author concluded on two things. Firstly, the larger the number of employees the worsen profit per employee and secondly , higher remuneration for commissioners and directors induced better profit per employee.  This study is limited in so far as it considers banking sector listed on Indonesia Stock Exchange only and conducted for only one financial year.